Advanced therapy medicinal products – special features of approval, application and monitoring Arzneimittel für neuartige Therapien – Besonderheiten der Zulassung, Anwendung und Überwachung - Rascher, Wolfgang (Pädiatrische Praxis, 2022)
Advanced therapy medicinal products, such as somatic gene therapy and cell therapy, have a high therapeutic potential for diseases that start very early in life and were previously untreatable. They are often approved at a very early stage of development, when efficacy has been impressively demonstrated in a small number of affected individuals and unprecedented therapeutic success is emerging. Early conditional approval raises new logistical, drug regulatory, and ethical issues for paediatrics. Diseases with very early manifestations in infancy must be diagnosed earlier than in the past, or even as part of newborn screening. Advanced therapy medicinal products have often not been used in sufficient numbers at the time of their approval, so that the necessary evidence for efficacy and safety is not yet available (benefit-risk ratio). For this reason, they are used under strict conditions in specialized treatment centers according to quality criteria defined by the Federal Joint Committee after consultation with the medical societies. Using therapy with advanced therapy medicinal products, as well as the documentation of its course, is considerable. Due to early, conditional approval, the value of an advanced therapy medicinal product becomes clear only with its broader use after approval, similar to the fact that the safety of a drug is not fully known with approval. Nonetheless, these advanced therapies offer great potential for diseases, particularly of children, that are currently untreatable or inadequately treatable.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cell therapy; drug approval; drug safety; gene therapy; newborn screening